2014
DOI: 10.1177/2325967114s00061
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Suprapectoral and Open Subpectoral Biceps Tenodesis: A Comparison of Minimum Two Year Clinical Outcomes

Abstract: Objectives:While a vast body of literature exists describing biceps tenodesis techniques and evaluating the biomechanical aspects of tenodesis locations or various implants, little literature presents useful clinical outcomes to guide surgeons in their decision to perform a particular method of tenodesis. The goal of this study is to compare the clinical outcomes of open subpectoral biceps tenodesis and arthroscopic suprapectoral tenodesis. Our null hypothesis is that both methods yield satisfactory results wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
86
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 0 publications
3
86
0
Order By: Relevance
“…In addition, the mean postoperative SANE was 89.9 (±15.3)., indicating a high level of satisfaction with the outcome of the procedure. These data were similar to those reported in previous series on isolated subpectoral tenodesis [42,43] [42]. Though many surgeons believe that a patient age over 65 is a contraindication to biceps tenodesis, the present study did not show an increased incidence of complications in this specific patient population whereas confirm the satisfactory outcomes previously reported in younger patients.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the mean postoperative SANE was 89.9 (±15.3)., indicating a high level of satisfaction with the outcome of the procedure. These data were similar to those reported in previous series on isolated subpectoral tenodesis [42,43] [42]. Though many surgeons believe that a patient age over 65 is a contraindication to biceps tenodesis, the present study did not show an increased incidence of complications in this specific patient population whereas confirm the satisfactory outcomes previously reported in younger patients.…”
Section: Discussionsupporting
confidence: 92%
“…33 The findings in this series are similar to those reported in the literature. Werner et al 35 In the 17 patients, the mean ASES score at an average 28-month follow-up was 78. They reported no instances of a change in the contour of the arm and no substantial complications.…”
Section: Discussionmentioning
confidence: 97%
“…9,10 Although there have been several biomechanical analyses of differing tenodesis techniques, 6,7,11,12 compelling clinical data showing the superiority of one technique over another have not yet been presented. Patzer et al 7 described a similar technique with a lasso loop Orthocord suture (DePuy Mitek, Raynham, MA) and a SwiveLock anchor (Arthrex).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Both open subpectoral and arthroscopic tenodesis techniques have been advocated in the literature. [3][4][5][6][7][8][9] In a biomechanical study comparing these 2 techniques, Mazzocca et al 6 found no difference in cyclic loading or yield to failure using different interference screw tenodesis strategies. In addition, no clinical difference has been found between arthroscopic suprapectoral biceps tenodesis and open subpectoral biceps tenodesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation